Copper powder and its manufacturing method
Patent Information
- Application Number
- JP2021073646
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-23
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-04-23
Smart Images

Figure 0007643921000027 
Figure 0007643921000028 
Figure 0007643921000001
Abstract
Description
[Technical field]
[0001] One embodiment of the present invention relates to copper powder and a method for making the copper powder. [Background technology]
[0002] Metal powders, which are aggregates of fine metal particles, are used in various fields, and metal powders and conductive pastes containing them are widely used as raw materials for manufacturing various electronic components, such as wiring and terminals of low-temperature co-fired ceramics (LTCC) substrates, and internal and external electrodes of multilayer ceramic capacitors (MLCCs). Copper powder in particular is expected to be a substitute for nickel and silver powders, which have been widely used in the past, because it is possible to thin the internal electrodes of MLCCs and to miniaturize the external electrodes, and it is possible to significantly improve frequency characteristics due to the high electrical conductivity of copper. For example, Patent Document 1 discloses that copper powders obtained by a gas phase method can be subjected to chlorine reduction treatment, oxygen reduction treatment, rust prevention treatment, etc., to produce copper powders with high purity and chemical stability. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6738460 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of one embodiment of the present invention is to provide copper powder and a method for producing the copper powder. For example, an object of one embodiment of the present invention is to provide copper powder having high resistance to oxidation and a method for producing the same. Alternatively, an object of one embodiment of the present invention is to provide high-purity copper powder having an extremely high circularity and an extremely low oxide content and a method for producing the same. [Means for solving the problem]
[0005] One embodiment of the present invention is a method for producing copper powder containing a plurality of copper particles, the method including: generating copper chloride gas by reacting metallic copper with a chlorine-containing gas; generating a plurality of copper particles by reacting the copper chloride gas with a reducing gas; and treating the plurality of copper particles with a treating agent containing a compound having a thiol group or a thioether group, and a carboxyl group in its molecule.
[0006] One embodiment of the present invention is a copper powder. The copper powder contains copper and a sulfur-containing compound. In this copper powder, the particle diameter D at which the cumulative frequency becomes 50% in a volume-based particle diameter histogram obtained by a laser diffraction scattering method is 50 is 0.1 μm or more and 0.5 μm or less. The content of cuprous oxide and cupric oxide in the copper powder obtained by X-ray diffraction method is less than 4 mass%. The average circularity of the copper powder is 0.97 or more. Here, the average circularity is the average circularity of the copper particles contained in the copper powder, and is calculated by the following formula. In the formula, A is the perimeter of the projected surface of the copper particle, and B is the perimeter of a circle having an area equal to the area of the projected surface.
number
[0007] [Figure 1] 1 is a flow chart for producing copper powder according to one embodiment of the present invention. [Diagram 2] X-ray photoelectron spectroscopy spectra of copper powder obtained in the examples and comparative examples DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, each embodiment of the present invention will be described with reference to the drawings, etc. The present invention can be embodied in various forms without departing from the spirit of the present invention, and should not be construed as being limited to the description of the embodiments exemplified below.
[0009] 1. Copper powder One embodiment of the present invention is a copper powder containing a plurality of copper particles (hereinafter, the copper powder according to this embodiment will be referred to as copper powder CP). As described later, the copper powder CP can be produced by a gas phase method. The characteristics of the copper powder CP will be described below.
[0010] 1-1.Particle size One of the characteristics of copper powder CP is that the particle diameter and its distribution are relatively small. Specifically, the particle diameter (median diameter) at which the cumulative frequency of the copper particles contained in the copper powder CP in the volume-based particle diameter histogram is 50% is small, and is 0.1 μm to 0.5 μm, 0.1 μm to 0.4 μm, or 0.1 μm to 0.3 μm. Here, the volume-based particle diameter is a particle diameter weighted by the volume of each copper particle contained in the copper powder CP. As expressed by the following formula, the frequency F of copper particles having the particle diameter di (i is a natural number from 1 to k, i≦k) is obtained by dividing the total volume of copper particles having the particle diameter di by the total volume of all copper particles contained in the copper powder CP. The particle diameter at which this frequency F is accumulated and reaches 50% is the median diameter.
[0011]
number
[0012] 1-2.Crystallite size Each copper particle contained in copper powder CP has a single or multiple crystallites. A crystallite is a region in each metal particle that can be regarded as a single crystal of metal, and can be determined using the Scherrer method. Specifically, the size of the crystallites of the copper particles, i.e., the average crystallite diameter D, can be obtained by substituting the parameters (wavelength λ of the X-rays used, half-width β of the spread of the diffracted X-rays, and Bragg angle θ) obtained by X-ray analysis of the metal powder, which is an aggregate of metal particles, into the Scherrer formula shown below. Here, K is the Scherrer constant.
[0013]
number
[0014] The production of copper powder by the gas phase method is useful for achieving a larger crystallite size compared to the production by the liquid phase method. Therefore, the copper powder CP has a large crystallite size relative to the particle size. As mentioned above, the multiple copper particles contained in the copper powder CP have a small median size. Therefore, the average crystallite size D relative to the median size (D / D 50 or D / DSEM 50 ) is large, for example, 0.10 to 0.50, 0.12 to 0.50, 0.20 to 0.50, 0.25 to 0.50, or 0.30 to 0.50.
[0015] 1-3. Purity (1) Copper oxide Representative metal powders include nickel powder and silver powder, but copper is more susceptible to surface oxidation than nickel and silver, and is more susceptible to oxidation by oxygen in the air to form oxides on the surface. Furthermore, this oxidation can progress to the inside of the copper particles. However, as described below, copper powder CP is treated with a compound containing sulfur and carbon (hereinafter also referred to as an antioxidant) to improve oxidation resistance. Due to the high oxidation resistance obtained by this treatment, the oxide content of copper powder CP is extremely low. Specifically, in the analysis of copper powder CP by X-ray diffraction (XRD), the respective contents of cuprous oxide (Cu2O) and cupric oxide (CuO) are less than 4 mass%, less than 3 mass%, or less than 1 mass%. In addition, this low oxide content is maintained for a long period after production. For example, as shown in the examples, even after several hours (e.g., 1 hour, 3 hours) have passed since production, the copper oxide content of less than 1 mass% can be maintained.
[0016] (2) Sulfur Due to the treatment with the antioxidant, the copper powder CP contains a trace amount of the antioxidant. The content of sulfur in the copper powder CP is 0.03% by mass or more and 5.0% by mass or less, 0.03% by mass or more and 0.4% by mass or less, or 0.2% by mass or more and 0.4% by mass or less. Since the antioxidant is present on the surface of the copper particles, the sulfur is also localized on the surface of the copper particles. Since the copper powder CP contains sulfur at the above-mentioned content, it exhibits high oxidation resistance and can prevent cracks and peeling during sintering when producing electronic components such as MLCC.
[0017] As described later, the antioxidant can contain a thiol group (-SH) in the molecule, and in this case, sulfur can exist as a thiol group in a state in which the antioxidant is adsorbed on the copper particle surface. That is, the antioxidant is adsorbed on the surface of the copper particle without forming a bond such as an ionic bond between S and Cu. Therefore, the copper powder CP can give a single peak derived from the 2p orbital of sulfur in the energy range of 160 eV to 166 eV in the X-ray photoelectron spectroscopy (XPS) spectrum. Specifically, the copper powder CP does not show multiple peaks in the above region, but shows one relatively broad peak.
[0018] The sulfur content in copper powder CP can be measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES) analysis or scanning transmission electron microscope-energy dispersive X-ray spectroscope (STEM-EDS) equipped with a scanning transmission electron microscope. In the former method, the copper powder CP is dissolved in an acid such as a mixed acid, and then ICP-AES analysis is performed at a measurement wavelength of 182.036 nm to obtain the bulk concentration of sulfur. In the latter method, the copper powder CP is dispersed in a resin and the resin is hardened. Then, a cross section is exposed using a cross-section polisher (CP), and a thin film sample is prepared by planar sampling using a focused ion beam (FIB). The thickness of the sample is set to about 100 nm, and the copper particles are formed into a thin film with this thickness. Then, EDS measurement is performed on the obtained thin film on a straight line passing through the center of the copper particles to obtain the local concentration of sulfur. The measurement conditions may be selected to be, for example, an acceleration voltage of 200 kV, a probe diameter of 1 nm, a pitch width of 3 nm, and a measurement time of 15 seconds per point.
[0019] (3) Carbon Due to the treatment with the antioxidant, the copper powder CP contains a small amount of carbon derived from the antioxidant. The carbon content in the copper powder is specifically 0.02% by mass to 1.5% by mass, 0.02% by mass to 1.2% by mass, or 0.10% by mass to 1.2% by mass. Since the copper powder CP contains carbon at the above-mentioned content, it exhibits high oxidation resistance and can prevent cracks and peeling during sintering when producing electronic components such as MLCCs.
[0020] The carbon content in copper powder can be measured by infrared absorption. For example, copper powder CP can be heated and melted in an inert gas such as argon, and the carbon monoxide generated can be introduced into an infrared analyzer and its absorption measured with a detector to determine the carbon content (inert gas fusion-infrared analysis). Alternatively, copper powder CP can be burned in a combustion furnace under an oxygen stream to generate carbon monoxide or carbon dioxide from the carbon in the copper powder CP. The generated carbon monoxide or carbon dioxide can be introduced into an infrared analyzer and its absorption measured with a detector to determine the carbon content (combustion infrared absorption method).
[0021] (4) Other elements Similarly, copper powder CP has a high copper purity with low content of other impurities. For example, the chlorine content is 5×10 -2 The lower limit of the chlorine content is 1×10 -4 Mass% or 5×10 -4 The chlorine content can be determined by coulometric titration.
[0022] 1-4.Shape Since the oxidation of copper particles progresses from the surface to the inside, the surface becomes uneven when oxidation occurs, and as a result, the circularity of the copper particles decreases. However, due to the high resistance of copper powder CP to oxidation, oxidation hardly occurs, and therefore the shape of the copper particles of copper powder CP is very close to a perfect sphere. More specifically, the average circularity AC of copper powder CP, i.e., the average circularity C of the copper particles, is very high, for example, 0.90 to 0.98 or 0.97 to 0.98.
[0023] Here, the average circularity AC is one of the parameters that express the shape of each copper particle contained in the copper powder CP, and is the average value of the circularity C of a plurality of copper particles (e.g., 500 particles) that are determined by analyzing an image obtained by observing the copper powder CP under a microscope. The circularity C is expressed by the following formula. Here, A is the perimeter of the projected surface of each copper particle in the microscope image, and B is the perimeter of a circle with an area equal to the area of this projected surface. Due to the high average circularity AC, the copper powder CP exhibits high packing ability.
number
[0024] As described above, since the copper powder CP has a small median diameter, thinner electrodes and wiring can be produced by using the copper powder CP. Furthermore, since copper has a higher electrical conductivity than nickel, which is one of the metals commonly used as metal powder, the use of the copper powder CP makes it possible to avoid an increase in electrical resistance even when electrodes and wiring are formed thin. Furthermore, since the copper powder CP has an extremely low content of impurities such as copper oxide and chlorine, the content of impurities that cause an increase in electrical resistance is low in wiring and electrodes produced using the copper powder CP. Therefore, LTCC substrates and the like with low wiring resistance can be produced. On the other hand, when the copper powder CP is used to produce an MLCC, the MLCC has a basic structure of a ceramic layer containing a dielectric material and a stack of internal electrodes containing a metal, and a pair of external electrodes connected to the internal electrodes, so that the internal electrodes can be made thinner and the external electrodes can be made smaller without causing an increase in electrical resistance due to the high electrical conductivity of copper, and it becomes possible to produce an MLCC with excellent frequency characteristics.
[0025] Furthermore, due to the small particle diameter of the copper particles, the copper powder CP has excellent dispersibility in an organic solvent, and when a paste containing the copper powder CP is used to form thin electrodes or wiring, the thickness variation is small, and wiring having a uniform thickness can be formed. In addition, unevenness is unlikely to occur on the electrodes or wiring, and electrodes or wiring having a flat surface can be formed. This prevents poor connection and increased connection resistance of electronic components, and contributes to improving the characteristics and reliability of electronic devices including electronic components.
[0026] When copper powder is used as a raw material for the internal electrodes of MLCCs, a dispersion containing a dielectric and a dispersion containing copper powder are alternately applied and then heated to sinter the copper powder and the dielectric. Generally, the sintering temperature of the dielectric is higher, so the copper powder is sintered first during sintering. As a result, a gap is generated between the dielectric and the internal electrode during sintering, and this gap may cause peeling between the internal electrode and the dielectric film. However, since the average crystallite diameter D of copper powder CP is large relative to the median diameter, the sintering temperature is high. For this reason, peeling during sintering can be suppressed. Therefore, by using copper powder CP, it is possible to provide MLCCs with a high yield. In addition, since copper powder CP has a low content of impurities that are likely to affect the sintering behavior and the properties of the film obtained by sintering, the occurrence of voids caused by impurities during sintering is also effectively suppressed.
[0027] 2. Manufacturing method An example of a method for producing copper powder CP will be described using the flow shown in Figure 1. Here, a method for producing copper powder CP using a so-called gas phase method will be described.
[0028] 2-1. Generation of copper chloride gas First, copper chloride gas is generated. One of the methods for generating copper chloride gas is heating copper chloride. In this method, solid copper chloride melts at high temperature to become liquid, and then vaporizes to become gas. For this reason, it is difficult to control the amount of copper chloride gas generated, and the supply amount of copper chloride gas in the subsequent reduction reaction tends to be unstable. As a result, it becomes difficult to control the median size, leading to an increase in particle size. In addition, if copper chloride once liquefied remains in the device (e.g., a heating furnace), the furnace may be destroyed due to contraction during cooling, so it is necessary to completely gasify almost all of the copper chloride.
[0029] For this reason, it is preferable to generate copper chloride gas by chlorinating metallic copper (i.e., zero-valent copper). This method not only allows the use of metallic copper, which is available at a lower cost than copper chloride, but also prevents the device from being damaged and stabilizes the supply amount of copper chloride gas. Specifically, copper chloride gas is generated by reacting metallic copper with chlorine at a temperature below its melting point (for example, 800°C to 1000°C). Hereinafter, the gas used for chlorination is referred to as the first chlorine-containing gas. The first chlorine-containing gas may substantially contain only chlorine, or may be a mixed gas of chlorine and an inert gas for dilution (hereinafter, referred to as the dilution gas). By using the dilution gas, the amount of chlorine can be easily and precisely controlled.
[0030] 2-2. Reduction of copper chloride Next, the generated copper chloride gas is treated with a reducing gas. Examples of the reducing gas that can be used include hydrogen, hydrazine, ammonia, and methane. The reducing gas is used in a stoichiometric amount or more relative to the copper chloride gas. For example, when the copper chloride gas is composed entirely of monovalent copper chloride and the reducing gas is hydrogen, the amount of the reducing gas introduced may be 50 mol% to 10,000 mol%, 500 mol% to 10,000 mol%, or 1,000 mol% to 10,000 mol% relative to the copper chloride gas. This treatment reduces the copper chloride to copper, and the generated copper element grows into copper particles to give copper powder. Hereinafter, the powder obtained by the reduction reaction is referred to as the primary powder.
[0031] As an optional step, chlorine may be added to the copper chloride gas before the reduction of the copper chloride gas. This is because the copper chloride gas and copper are in equilibrium as shown below, and a part of the copper chloride produced returns to copper. If copper precipitates or liquefies due to this equilibrium, it will induce blockage, clogging, or destruction of the equipment for producing copper powder CP. Furthermore, if the concentration of the copper chloride gas decreases due to this equilibrium, the amount of copper chloride gas used in the reduction reaction will fluctuate. However, by adding chlorine to the copper chloride gas, this equilibrium will shift to the copper chloride side, and the occurrence of the above-mentioned problems can be suppressed. Hereinafter, the gas used to shift this equilibrium will be referred to as the second chlorine-containing gas. As with the first chlorine-containing gas, the second chlorine-containing gas may contain substantially only chlorine, or may contain a diluent gas and chlorine. The chlorine added here does not contribute significantly to the chlorination of metallic copper, so its volume may be smaller than the volume of chlorine contained in the first chlorine-containing gas. For example, the volume of chlorine contained in the second chlorine-containing gas may be 0.001% to 20%, or 0.01% to 10%, or 0.1% to 2% of the volume of chlorine contained in the first chlorine-containing gas.
[0032] [ka]
[0033] When chlorine is added to copper chloride gas, the temperature (second temperature) of the mixed gas of copper chloride gas and the second chlorine-containing gas may be higher than the temperature (first temperature) at which copper chloride gas is generated. By setting the mixed gas temperature at a higher temperature, the reverse reaction of generating copper from copper chloride gas can be more effectively suppressed. For example, the generation of copper chloride can be performed at a temperature selected in the range of 800°C to 1000°C, and the temperature of the mixed gas can be selected in the range of 1000°C to 1300°C. The difference between these temperatures may be, for example, 100°C to 400°C, 150°C to 350°C, or 200°C to 300°C. This makes it possible to more effectively prevent the copper chloride from liquefying in the manufacturing equipment.
[0034] When the second chlorine-containing gas is introduced, the particle size of the copper powder CP can be controlled by adjusting the amount of the dilution gas. For example, the median size can be reduced by setting the volume ratio (Cl2:dilution gas) to 5:95 or more and 40:60 or less, or 5:95 or more and 30:70 or less, or 10:90 or more and 25:75 or more. As a result, a copper powder CP having a high average circularity AC and a large average crystallite size D relative to the median size can be obtained.
[0035] 2-3. Reduction of chlorine content When copper chloride is reduced with a reducing agent such as hydrogen, hydrogen chloride is produced along with the primary powder of the metal. Hydrogen chloride can also be produced when unreacted chlorine in the first chlorine-containing gas or chlorine in the second chlorine-containing gas reacts with a reducing gas. For this reason, the resulting primary copper powder can react with hydrogen chloride, resulting in the formation of copper chloride on the surface. This problem also occurs when other metals are used, but since the solubility of copper chloride in water is low (0.0236 g / 100 mL) compared to that of nickel chloride (54 g / 100 mL), simply purifying with water can result in a large amount of copper chloride remaining in the primary powder. This is one of the causes of the decrease in purity of copper powder CP.
[0036] Therefore, in one embodiment of the present invention, the primary copper powder obtained after reduction may be subjected to copper chloride removal or reduction in chlorine content (hereinafter, the removal of copper chloride and reduction in chlorine content are collectively referred to as reduction in chlorine content). The reduction in chlorine content may be performed by treating the primary powder with a cleaning liquid, and the cleaning liquid may be an aqueous solution or suspension of a base. The base may be an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide. The cleaning liquid may contain two types of hydroxide. The base concentration of the cleaning liquid may be 0.1M or more, or 0.5M or more, and 1.5M or less, or 1.2M or less.
[0037] 2-4. Reduction of oxygen content Although copper has a lower tendency to ionize than nickel, the oxidation of copper is more likely to progress not only on the surface but also to the inside than the oxidation of nickel, and therefore oxidation may progress before the antioxidant treatment described below, for example during the treatment to reduce the chlorine content.
[0038] Therefore, in this embodiment, the primary powder may be subjected to a treatment for removing copper oxide or reducing the oxygen content (hereinafter, the removal of copper oxide and the reduction of the oxygen content are collectively referred to as the reduction of the oxygen content). This treatment may be performed after the reduction of the chlorine content. The reduction of the oxygen content can be performed by treating the primary powder with a solvent containing ascorbic acid, hydrazine, citric acid, etc., washing with water, filtering, and drying. Examples of the solvent in the solvent include water, alcohols such as ethanol and isopropyl alcohol, ketones such as acetone and methyl ethyl ketone, and mixed solvents of these. When ascorbic acid is used, the concentration of ascorbic acid in the cleaning solution may be 5% by mass or more, or 10% by mass or more, and 25% by mass or less, or 20% by mass or less. Copper oxide can be removed by this operation.
[0039] 2-5. Oxidation resistance improvement treatment In the method for producing copper powder according to an embodiment of the present invention, a treatment for improving oxidation resistance (oxidation resistance improvement treatment) is performed on the primary powder produced by the reduction of copper chloride. The oxidation resistance improvement treatment may be performed after the chlorine content or oxygen content reduction treatment, or may be performed on the primary powder that has not been subjected to the chlorine content or oxygen content reduction treatment. The oxygen content reduction treatment also reduces the surface irregularities caused by the generation of copper oxide, and a copper powder CP having high average circularity and packing properties can be obtained. However, by performing this oxidation resistance improvement treatment, the oxidation of the copper particles is extremely effectively suppressed, and as a result, a higher average circularity and packing properties can be obtained.
[0040] The oxidation resistance improvement treatment is carried out by treating the primary powder with a treatment agent containing an antioxidant. The antioxidant contains carbon and sulfur. Specifically, the antioxidant has a thiol group (SH) or a thioether group (-S-), and a carboxyl group (CO2H) in the molecule. The antioxidant may contain two or more thiol groups and two or more carboxyl groups in the molecule. For example, one of the antioxidants is a compound represented by the following general formula (1).
[0041] [ka] (1)
[0042] In the general formula (1), n is 1 or 2. 1 and R 2 are each independently selected from hydrogen, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, a substituted or unsubstituted cycloalkyl group having 5 or more carbon atoms, a substituted or unsubstituted aromatic group, a carboxyl group, an amide group having 1 to 4 carbon atoms, halogen, an amino group having an alkyl group having 1 to 4 carbon atoms, a diarylamino group, and a substituted or unsubstituted alkoxy group having 1 to 4 carbon atoms. 3 is selected from hydrogen, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, a substituted or unsubstituted cycloalkyl group having 5 or more carbon atoms, a substituted or unsubstituted aromatic group, and the like.
[0043] More specifically, the compounds represented by the following chemical formulas can be used as the antioxidant. However, compounds other than the following compounds may also be used.
[0044] [ka]
[0045] [ka]
[0046] [ka]
[0047] [ka]
[0048] [ka]
[0049] [ka]
[0050] [ka]
[0051] [ka]
[0052] Alternatively, one of the antioxidants may be a compound represented by the following general formula (2):
[0053] [ka] (2)
[0054] In general formula (2), A is an aliphatic ring or an aromatic ring, and the sulfur of a thiol group or a thioether group is bonded to the carbon (α carbon) adjacent to the ring carbon bonded to the carboxyl group carbon. 4 is selected from hydrogen, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, a substituted or unsubstituted cycloalkyl group having 5 or more carbon atoms, and a substituted or unsubstituted aromatic group. 5is selected from hydrogen, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, a substituted or unsubstituted cycloalkyl group having 5 or more carbon atoms, a substituted or unsubstituted aromatic group, a carboxyl group, an amido group having 1 to 4 carbon atoms, halogen, an amino group having an alkyl group having 1 to 4 carbon atoms, a diarylamino group, and a substituted or unsubstituted alkoxy group having 1 to 4 carbon atoms.
[0055] More specifically, the compounds represented by the following chemical formulas can be used as the antioxidant. However, compounds other than the following compounds may also be used.
[0056] [ka]
[0057] [ka]
[0058] [ka]
[0059] The aromatic group in formulas (1) and (2) may be an aromatic hydrocarbon or a heteroaromatic group, such as a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, a pyridyl group, a phenanthryl group, a diazolyl group, a triazolyl group, a thiophenyl group, or a benzothiophenyl group. Substituents of the substituted alkyl group, substituted cycloalkyl group, substituted aromatic group, and substituted alkoxy group may be, for example, an alkyl group having 1 to 4 carbon atoms or a halogen such as fluorine. The alkyl group may be linear or branched.
[0060] The treatment agent in the oxidation resistance improving treatment contains the above-mentioned antioxidant and a solvent. The solvent may be water, alcohols such as methanol, ethanol, and isopropanol, ketones such as acetone and methyl ethyl ketone, ethers such as tetrahydrofuran and dioxane, and amides such as N,N-dimethylformamide and N,N-dimethylacetamide. Water is particularly preferable because it is inexpensive and non-toxic. The concentration of the antioxidant is, for example, 1.0×10 -4 It can be adjusted in the range of M to 1.0M.
[0061] The oxidation resistance improving treatment is carried out by mixing the treatment agent and the primary powder and stirring. The treatment temperature is, for example, from 0°C to 30°C, and is typically room temperature (25°C or thereabouts). The stirring time may be appropriately selected from 1 minute to 1 hour, or 5 minutes to 30 minutes. After stirring is completed, the treatment agent is removed by filtration or decantation, and the mixture is washed with water and then dried to obtain copper powder CP.
[0062] By carrying out the oxidation resistance improving treatment, as shown in the examples, the copper powder CP is hardly oxidized, and as a result, the contents of cuprous oxide and cupric oxide obtained by X-ray diffraction method are less than 4 mass%, less than 3 mass%, or less than 1 mass%, respectively. Furthermore, the contents of cuprous oxide and cupric oxide in the copper powder CP that has been left to stand in the atmosphere for a certain period of time after production are also less than 4 mass%, less than 3 mass%, or less than 1 mass%, respectively. This suggests that high oxidation resistance can be maintained for a long period of time by the oxidation resistance improving treatment.
[0063] 2-6.Other processes As an optional step, the obtained copper powder CP may be subjected to steps such as classification, crushing, and sieving.
[0064] The classification may be either a dry classification or a wet classification, and in the case of dry classification, any method can be used, such as air classification, gravity field classification, inertial field classification, centrifugal field classification, etc. Similarly, in the case of wet classification, methods such as gravity field classification and centrifugal field classification can be used.
[0065] For example, classification can be performed by low-temperature airflow classification using lower alcohols with carbon numbers of 1 to 3, such as methanol, ethanol, n-propanol, and isopropanol, or alcohols with a vapor pressure of 18.7 hPa or more at 20°C. In this case, the copper powder CP is first sprayed with alcohol or treated with alcohol vapor. At this time, it is preferable that 40% to 1000% of the saturated adsorption amount of alcohol is adsorbed on the copper powder CP. Thereafter, classification is performed under conditions where the classification temperature is kept at 0°C to 35°C and the classification pressure is 0.2 MPa to 0.8 MPa, or 0.3 MPa to 0.6 MPa.
[0066] The crushing process may be performed using, for example, a jet mill. In the sieving process, a sieve having a desired mesh size is vibrated and the copper powder CP is passed through it. By performing classification, crushing, and sieving processes, it is possible to make the particle size and its distribution of the copper powder CP smaller.
[0067] The copper powder CP is produced by the above steps. As described above, in the production method of this embodiment, oxidation resistance improvement treatment is performed. As a result, the copper oxide content of the copper powder CP is extremely low, and as a result, copper powder CP containing copper particles with extremely high average circularity and single crystallinity and having a small particle size can be obtained. EXAMPLES
[0068] The following describes the manufacture of copper powder CP and its characteristics. Here, we explain an example in which primary copper powder was produced using a gas phase method, and the primary powder was subjected to treatment to reduce the chlorine and oxygen contents and to improve the oxidation resistance.
[0069] 1. Example 1-1. Preparation of primary powder Metallic copper pellets were placed in a chlorination furnace with a quartz vaporization aid placed on the floor. The chlorination furnace was heated to 900°C, and a heating furnace connected to the chlorination furnace and into which copper chloride gas was introduced was heated to 1150°C, and chlorine-containing gases containing chlorine and nitrogen (first and second chlorine-containing gases, respectively) were introduced from the top and bottom of the chlorination furnace. The volume ratio of the first and second chlorine-containing gases introduced from the top and bottom of the chlorination furnace, respectively, was 1:0.17, and the volume ratio of chlorine to nitrogen (Cl2:N2) was 29:61 and 2:98, respectively.
[0070] The copper chloride gas produced by chlorination was introduced into a reduction furnace connected to a heating furnace, and while the reduction furnace was heated to 1150°C, 4600 mol% hydrogen and 24600 mol% nitrogen were introduced relative to the copper chloride gas. The produced copper particles were cooled using nitrogen gas.
[0071] Subsequently, a process for reducing the chlorine content and oxygen content was carried out. Specifically, about 300 mL of 1 M sodium hydroxide aqueous solution was added as a washing solution to 30 g of the obtained primary powder, and the mixture was stirred at room temperature for 10 minutes. After stirring, the supernatant was removed, and the primary powder was washed with water until the pH reached 7, and then dried. After this, an aqueous solution (about 300 mL) containing 6 g of ascorbic acid was added, and the obtained mixture was stirred at room temperature for 30 minutes. After stirring, the mixture was filtered, and the product was washed four times with water (about 500 mL), and then dried.
[0072] 1-2. Treatment to improve oxidation resistance Furthermore, 0.00094M antioxidant aqueous solution (approximately 300mL) was added as a treatment agent to 30g of the primary powder, and stirred at room temperature for 30 minutes. After stirring, the supernatant was removed, and the mixture was washed with water (approximately 500mL) four times. The obtained copper particles were dried to obtain copper powder CP. As antioxidants, mercaptosuccinic acid (A), mercaptoacetic acid (B), 3-mercaptopropionic acid (C), and thiosalicylic acid (D), shown in the following chemical formula, were used. The type of antioxidant and the concentration of the antioxidant aqueous solution were changed as shown in Table 1 to obtain samples of Examples 1 to 12.
[0073] [ka]
[0074] 2. Comparative Example For Comparative Examples 1 to 8, in the oxidation resistance improvement treatment in the above Examples, thiourea (E), benzotriazole (F), and a mixture containing thiourea and succinic acid ((G), molar ratio: 1:1) shown below were used as blank compounds instead of antioxidants, and the primary powder was treated with these aqueous solutions. The treatment conditions were the same as those for the oxidation resistance improvement treatment using antioxidants. The type of the blank compound and the concentration of its aqueous solution were changed as shown in Table 1 to obtain samples of Comparative Examples 1 to 8. [ka]
[0075] In addition, as Comparative Example 9, a primary powder obtained by a wet method was prepared and subjected to the same treatment as in the Examples. The preparation of the primary copper powder by the wet method was performed according to the description in JP 2003-342621 A. As in Example 1, 30 g of this primary powder was subjected to a treatment to reduce the chlorine content and oxygen content, and a treatment to improve the oxidation resistance.
[0076] 3. Evaluation The sulfur content was measured using an inductively coupled plasma emission spectrometer (SPS3100) manufactured by SII Nano Technology Co., Ltd. The carbon content was measured using a carbon and sulfur analyzer (EMIA-920V2) manufactured by Horiba, Ltd. in accordance with JIS H1617 and JIS Z2615. The copper oxide content, crystallite size, and median diameter D 50The measurement was performed using an X-ray diffractometer (X'Pert Pro) manufactured by Spectris Inc. (CuKα radiation, acceleration voltage 45 kV, discharge current 40 mA). The projection image of the copper powder was obtained using a scanning transmission electron microscope (JEM-2100F manufactured by JEOL Ltd.). The average circularity was obtained by analyzing approximately 500 copper particles present in one field of view of a scanning transmission electron microscope image at a magnification of 15,000 times using image analysis software (Macview 4.0 manufactured by Mountec Co., Ltd.). The bonding state of sulfur atoms on the copper powder was measured using an X-ray photoelectron spectrometer (k-alpha+ manufactured by Thermo Fisher Scientific Co., Ltd.). The results are shown in Table 1. In Table 1, the content of cuprous oxide and cupric oxide is shown as less than 1 mass% (<1), which means that it was below the lower limit of detection in the above measurement.
[0077] [Table 1]
[0078] As can be seen from all the Examples and Comparative Examples 1 to 8, the median diameter D 50 is small, which leads to a large difference in the average crystallite size relative to the median size (D / D 50 On the other hand, the copper powder of Comparative Example 9 produced by the wet method has a large D / D 50 This indicates that the gas phase method can provide copper powder with a small particle size and a high sintering initiation temperature.
[0079] As an example, the XPS spectra of the copper powder CP of Example 1 and Comparative Example 1 are shown in FIG. 2(A). For reference, the XPS spectra of cuprous sulfide and cupric sulfide are shown in FIG. 2(B). As shown in FIG. 2(A), the copper powder of Comparative Example 1 using thiourea gives two sharp peaks derived from the 2s orbital of sulfur in the energy range of 160 eV to 166 eV. These two peaks almost coincide with the peaks of the spectra of cuprous sulfide and cupric sulfide (FIG. 3(B)). This indicates that the sulfur of thiourea forms an ionic bond with copper and exists as copper sulfide. On the other hand, the copper powder CP of Example 1 does not show multiple peaks in the same energy range, but gives a relatively broad single peak. This suggests that the sulfur of mercaptosuccinic acid does not form an ionic bond with copper on the copper particles and exists as a thiol group.
[0080] As shown in Table 1, when comparing the sulfur contents of Examples 1, 5, and 9, it can be seen that the sulfur content and carbon content increase with increasing concentration of the antioxidant aqueous solution. A similar tendency was confirmed in the comparison of Examples 2, 6, and 10, the comparison of Examples 3, 7, and 11, and the comparison of Examples 4, 8, and 12. Furthermore, in the comparison of Comparative Examples 1, 4, and 7, the comparison of Comparative Examples 2 and 5, and the comparison of Comparative Examples 3, 6, and 8, it was confirmed that the sulfur content and carbon content increase with increasing concentration of the aqueous solution of the blank compound. However, since blank compound F does not contain sulfur, sulfur was not substantially detected (Comparative Examples 2 and 5). This means that the sulfur and carbon detected in copper powder CP are derived from the antioxidant, and their contents can also be controlled by the concentration of the aqueous solution of the antioxidant.
[0081] In addition, when comparing the samples of Examples 1 to 4, it was confirmed that the sulfur content of copper powder CP was constant regardless of the antioxidant, but the carbon content increased in the order of antioxidants B, C, A, and D. This tendency does not depend on the concentration of the antioxidant aqueous solution, as can be seen from the comparison of Examples 5 to 8 and Examples 9 to 12. The reason for this is that although antioxidants A to D all contain one sulfur atom in the molecule, the number of carbon atoms increases in the order of B, C, A, and D. In fact, the number of carbon atoms of antioxidants B, C, A, and D are 2, 3, 4, and 7, respectively. This means that the sulfur and carbon contents detected in copper powder CP can be independently controlled not only by the concentration of the antioxidant aqueous solution but also by the type of antioxidant.
[0082] The contents of cuprous oxide and cupric oxide in all the samples in the examples were below the lower limit of detection by the X-ray diffraction method 1 hour after the completion of the oxidation resistance improvement treatment. In addition, in the samples in Examples 1 to 4 in which the concentration of the antioxidant aqueous solution was low, an increase in the content of cuprous oxide was confirmed 3 hours after the start of storage in an atmosphere at a temperature of 25°C and a humidity of 50%, but the contents of cuprous oxide in the other Examples 5 to 12 all remained below the lower limit of detection. In contrast, as can be seen from the results of Comparative Examples 1 to 8, when a blank compound that does not simultaneously have a thiol group or a thioether group and a carboxyl group in the molecule was used, the content of cupric oxide was low, but a high content of cuprous oxide was shown even 1 hour after production. In addition, the content of cuprous oxide increased with time, and for example, it was found that the sample in Comparative Example 1 contained as much as 10% by mass of cuprous oxide 3 hours after the start of storage. In addition, in the copper powder produced by applying a wet method (Comparative Example 9), cupric oxide was detected even 1 hour after production.
[0083] Here, when comparing Comparative Examples 4 and 6 in which the aqueous solution concentration of the blank compound is the same, there is no difference in the sulfur content, but the carbon content is different. The same can be said from a comparison between Comparative Examples 7 and 8. This means that in Comparative Examples 6 and 8, not only thiourea but also succinic acid is present on the copper particle surface. However, the oxidation resistance of the obtained copper powder is low, and it shows a high cuprous oxide content compared to the examples. These results indicate that the high oxidation resistance of the copper powder CP according to the embodiment of the present invention is not simply due to the independent contribution of the thiol group or thioether group and the carboxyl group, but is expressed due to the simultaneous concerted contribution of these functional groups.
[0084] Due to its high oxidation resistance, the copper powder CP exhibits an extremely high circularity and does not change over time for at least 3 hours. In contrast, in all of Comparative Examples 1 to 9, the average circularity is not only low immediately after production, but also decreases over time. These results clearly show that although copper has the property of being easily oxidized in the atmosphere, in the copper powder CP according to the embodiment of the present invention, the oxidation of copper does not progress or is negligible.
[0085] As described above, it has been found that application of the embodiments of the present invention makes it possible to provide copper powder having extremely high purity, average circularity, and high oxidation resistance.
[0086] The above-described embodiments of the present invention may be combined as appropriate as long as they are not mutually inconsistent. Furthermore, those in which a person skilled in the art appropriately adds or removes components or modifies designs, or adds or omits steps or modifies conditions, based on each embodiment, are also included in the scope of the present invention as long as they include the gist of the present invention.
[0087] Even if there are other effects and advantages different from those brought about by the aspects of each of the above-mentioned embodiments, those which are clear from the description in this specification or which can be easily predicted by a person skilled in the art are naturally understood to be brought about by the present invention.
Claims
1. A method for producing copper powder containing copper and a sulfur-containing compound, comprising the steps of: a particle diameter D50 at which a cumulative frequency of 50% in a volume-based particle diameter histogram of the copper powder obtained by a laser diffraction scattering method is 0.1 μm or more and 0.5 μm or less; The copper powder has a cuprous oxide and cupric oxide content of less than 4% by mass as determined by X-ray diffraction method; The copper powder has an average circularity of 0.97 or more, The average circularity is an average of the circularities of a plurality of copper particles contained in the copper powder, The circularity is calculated by the following formula: [0010] A is the perimeter of the projected surface of the copper particle, and B is the perimeter of a circle having an area equal to the area of the projected surface, The sulfur-containing compound is localized on the surface of the copper powder, The sulfur content is 0.03% by mass or more and 5.0% by mass or less, and the carbon content is 0.02% by mass or more and 1.5% by mass or less, The method comprises: reacting metallic copper with a chlorine-containing gas to produce copper chloride gas; generating a plurality of copper particles by reacting the copper chloride gas with a reducing gas; treating the plurality of copper particles with a treating agent comprising a compound having a thiol or thioether group and a carboxyl group in its molecule.
2. The method according to claim 1 , wherein the compound has two carboxyl groups in the molecule.
3. The compound is represented by the following general formula: 【Chemistry 1】 n is 1 or 2; R 1 and R 2 are each independently selected from hydrogen, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, a substituted or unsubstituted cycloalkyl group having 5 or more carbon atoms, a substituted or unsubstituted aromatic group, a carboxyl group, an amido group having 1 to 4 carbon atoms, halogen, an amino group having an alkyl group having 1 to 4 carbon atoms, a diarylamino group, and a substituted or unsubstituted alkoxy group having 1 to 4 carbon atoms; R 3 is a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, or a substituted group having 5 or more carbon atoms.
2. The method of claim 1, wherein the alkyl group is selected from the group consisting of a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aromatic group, and a substituted or unsubstituted aromatic group.
4. The method of claim 1 , wherein the compound has the general formula: 【Chemistry 2】 。
5. The compound is represented by the following general formula: 【Chemistry 3】 A is an aliphatic ring or an aromatic ring; R 4 represents hydrogen, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, or a substituted group having 5 or more carbon atoms. or an unsubstituted cycloalkyl group, or a substituted or unsubstituted aromatic group; R 5 is a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, or a substituted group having 5 or more carbon atoms.
2. The method according to claim 1 , wherein the alkyl group is selected from the group consisting of a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aromatic group, a carboxyl group, an amide group having 1 to 4 carbon atoms, halogens, an amino group having an alkyl group having 1 to 4 carbon atoms, a diarylamino group, and a substituted or unsubstituted alkoxy group having 1 to 4 carbon atoms.
6. The method of claim 1, wherein the compound is selected from mercaptosuccinic acid, mercaptoacetic acid, 3-mercaptopropionic acid, and thiosalicylic acid.
7. 10. The method of claim 1, further comprising treating the plurality of copper particles with a base prior to said treating with said treating agent.
8. The method of claim 1, further comprising treating the plurality of copper particles with at least one selected from ascorbic acid, hydrazine, and citric acid prior to said treatment with said treating agent.
9. It is a copper powder containing copper and sulfur-containing compounds. The particle diameter D at which the cumulative frequency becomes 50% in a volume-based particle diameter histogram obtained using a laser diffraction scattering method 50 is 0.1 μm or more and 0.5 μm or less, The content of cuprous oxide and cupric oxide obtained by X-ray diffraction method is less than 4 mass %, The average circularity is 0.97 or more, The average circularity is an average of the circularities of copper particles contained in the copper powder, The circularity is calculated by the following formula: [0010] A is the perimeter of the projected surface of the copper particle, and B is the perimeter of a circle having an area equal to the area of the projected surface, The sulfur-containing compound is localized on the surface of the copper powder, A copper powder having a sulfur content of 0.03% by mass or more and 5.0% by mass or less and a carbon content of 0.02% by mass or more and 1.5% by mass or less.
10. 10. The copper powder according to claim 9, wherein the content of cuprous oxide and cupric oxide is less than 1 mass% as measured by the X-ray diffraction method.
11. The copper powder according to claim 9, wherein the sulfur of the sulfur-containing compound is present as a thiol group.
12. The sulfur content is 0.03% by mass or more and 0.40% by mass or less, The copper powder according to claim 9, having a carbon content of 0.02% by mass or more and 1.5% by mass or less.
Citation Information
Patent Citations
Copper alloy powder, manufacturing method therefor, copper alloy powder superior in oxidation resistance for electroconductive paste and manufacturing method therefor
JP2005097716A
Method for producing copper powder
JP2020180329A
Copper powder manufacturing method
JP6738460B1
Metal microparticle dispersion, process for production of electrically conductive substrate, and electrically conductive substrate
WO2011040189A1
Metal particles, method for manufacturing same, coated metal particles, and metal powder
WO2016170904A1